2021
DOI: 10.1001/jama.2020.26498
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Vitamin D Deficiency in Adults

Abstract: IMPORTANCE Low serum vitamin D levels have been associated with adverse clinical outcomes; identifying and treating deficiency may improve outcomes.OBJECTIVE To review the evidence about screening for vitamin D deficiency in adults.DATA SOURCES PubMed, EMBASE, the Cochrane Library, and trial registries through March 12, 2020; bibliographies from retrieved articles, outside experts, and surveillance of the literature through November 30, 2020.STUDY SELECTION Fair-or good-quality, English-language randomized cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 95 publications
3
47
0
3
Order By: Relevance
“…This review found minimal other recent synthesized evidence on the effect of multivitamin use, but another review concluded that observational studies suggest a possible lower breast cancer recurrence among breast cancer survivors using multivitamins . The findings for vitamin D in the current review are generally consistent with those from other reviews, for example, pooled estimates in the range of 0.93 to 0.97 that may not be statistically significant for all-cause mortality . In general, the statistical significance of an all-cause mortality benefit in pooled analyses is unstable, being sensitive to the number of included studies and which study aims are considered.…”
Section: Discussionsupporting
confidence: 77%
“…This review found minimal other recent synthesized evidence on the effect of multivitamin use, but another review concluded that observational studies suggest a possible lower breast cancer recurrence among breast cancer survivors using multivitamins . The findings for vitamin D in the current review are generally consistent with those from other reviews, for example, pooled estimates in the range of 0.93 to 0.97 that may not be statistically significant for all-cause mortality . In general, the statistical significance of an all-cause mortality benefit in pooled analyses is unstable, being sensitive to the number of included studies and which study aims are considered.…”
Section: Discussionsupporting
confidence: 77%
“…Recent RCTs have not demonstrated the benefit in the use of vitamin D supplementation for the prevention of depression [ 39 ] or reduction of episodes of MDD [ 40 ]. In a recent US Preventive Services Task Force report, it was noted that populations with specific clinical conditions to evaluate treatment of deficiency for alleviation of their symptoms were not included [ 41 ]. Thus, the study of vitamin D for symptom relief in persons with chronic conditions is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review did not find any studies directly evaluating the benefits of screening for vitamin D deficiency. 84 Hence, routine testing of vitamin D levels in community‐dwelling older adults may be undertaken upon careful consideration of feasibility and applicability, and in resource‐limited settings, a more targeted approach may be reasonable, for example, screening for suspected osteoporosis.…”
Section: Nutritional Supplementationmentioning
confidence: 99%